STUDY OF IMAGE DESIGN CONCEPT FOR MODERN THAI IMMUNIZATION CUISINE IN NEW NORMAL LIFESTYLE - Latthitham, Peeraphan; Wanichakorn, Aran; Boonyadacho, Naddawadee (Dusit Thani College Journal, 2021)
This research is concerned with study of image design concept for modern Thai immunization cuisine in New normal era has the following aims: (1) to study the properties of Thai herbs as an ingredient in Thai immunization cuisine; (2) to design images of modern Thai immunization cuisine to harmonize with the New Normal lifestyle by research papers and interviews with specialists, and to analyze and synthesize knowledge and develop new products and evaluated by specialists. The results were divided into two sections: Section One was the knowledge and the principles of Thai immunization cuisine, which was divided into three principles: cleanliness or maintaining hygiene and cleaning standards, freshness or using fresh and using quality ingredients; and herbs or using Thai herbs in the food and on the menu. Section Two was product development by applying the principles of Thai immunization cuisine concept.